Investigation of Two Potential Predictors of Thrombosis Risk in Polycythemia Vera: Hematocrit-to-Hemoglobin Ratio and HALP Score - Deniz Yilmaz MD; Eyyup Akkaya MD (Clinical and Applied Thrombosis/Hemostasis)
Objective: This study aimed to assess the utility of the hematocrit-to-hemoglobin ratio (HHR) and the HALP score in detecting thrombosis history in patients with polycythemia vera (PV). Methods: This retrospective study examined patients diagnosed with PV between January 2013 and December 2022. Demographics, clinical history, PV- and thrombosis-related data, laboratory findings, follow-up duration, and mortality status were retrieved from hospital records. HHR and HALP scores were calculated for all patients. Patients were grouped based on their thrombosis history. Results: A total of 124 PV patients were included, with a mean age of 57.65 ± 12.17 years, and 86 (69.35%) were males. Thrombosis was present in 59 patients (47.58%), with 32.20% occurring before diagnosis, 23.73% at diagnosis, and 44.07% after diagnosis. Patients with and without thrombosis history were similar in age and sex. Those with a history of thrombosis had significantly higher anticoagulant use and HHR values, while other variables, including HALP score, showed no differences. An HHR cut-off value of >3.05 predicted thrombosis history with 54.24% sensitivity and 72.31% specificity. Conclusion: HHR could help distinguish PV patients with thrombosis history, though its sensitivity is low. HALP score was not associated with thrombosis risk.